Acid Rain Contribution from Pesticide Distribution to Rice Farmers in Pati Regency - Qosim Ahmad; Anies; Rya Sunoko Henna (E3S Web of Conferences, 2018)
Productivity rate of rice fields in Regency has been in a surplus condition annually. The fields have produced 7 to 8 tons per hectare, making the total annual rate of 600 tons. The regency, therefore, is considered to be capable of fulfilling its own need for rice and to contribute significantly to the rice needs in Central Java Province. Agriculture coexists with the presence of pesticides. While helping the farmers to combat the plant diseases, pesticides have still been greatly necessary by the local farmers. Distribution by means of transportation devices plays an important role for the dissemination of the pesticides from the producers to their end users. Problem arises due to emission produced during the transportation activities. Transportation emits SO2 as the major contributor to acid rain. To make worse, application in practice by the farmers also emit the similar substance. Annual use of pesticides in Pati Regency has reached 605 tons with SO2 emission of 13,697 kg. It is recommended that distribution management and selection of pesticides are performed by applying an integrated pest control in order to reduce the pesticide emission.